2014
DOI: 10.1124/mol.114.093450
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Monitoring ofμ-Opioid Receptor–Mediated Signaling

Abstract: In this study, we used a combination of traditional signaling investigation approaches, bioluminescence resonance energy transfer (BRET) biosensors, and the label-free approach surface plasmon resonance (SPR) spectroscopy to monitor the signaling cascades of the m-opioid receptor (MOP). In human embryonic kidney cells stably expressing a Flag-tagged version of human MOP, we compared the signals triggered by the noninternalizing and internalizing MOP agonists morphine and DAMGO (Tyr-DAla-Gly-N-methyl-Phe-Gly-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Although some reports have described the capacity of AT1R to couple to Gi, to our knowledge coupling to Gs has not been found. Therefore, we only assessed the contributions of the Gi pathway using the inhibitor of Gi activation, PTX, an approached used previously by our group in a study of mu-opioid receptor signalling by SPR [27]. As shown in Fig.…”
Section: Contribution Of Gi and Gβγ In Angii-mediated Spr Cell Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Although some reports have described the capacity of AT1R to couple to Gi, to our knowledge coupling to Gs has not been found. Therefore, we only assessed the contributions of the Gi pathway using the inhibitor of Gi activation, PTX, an approached used previously by our group in a study of mu-opioid receptor signalling by SPR [27]. As shown in Fig.…”
Section: Contribution Of Gi and Gβγ In Angii-mediated Spr Cell Responsementioning
confidence: 99%
“…Surface Plasmon Resonance (SPR) was previously validated by our group as detection method to monitor live cells responses to various GPCRs stimulations [26,27]. In our previous work, using confocal microscopy and SPR-based imaging to monitor actin cytoskeleton remodelling and atomic force microscopy to quantify cell contraction, we have shown that early events of the AT1R-dependent responses are associated with cell body contraction whereas the later phase of the response involves actin mobilization and extensive spreading of the cell [26].…”
Section: Introductionmentioning
confidence: 99%